2015
DOI: 10.1007/s00394-015-0955-5
|View full text |Cite
|
Sign up to set email alerts
|

Intake of water and beverages of children and adolescents in 13 countries

Abstract: PurposeTo describe the intake of water and all other beverages in children and adolescents in 13 countries of three continents. MethodsData of 3611 children (4–9 years) and 8109 adolescents (10–17 years) were retrieved from 13 cross-sectional surveys (47 % males). In three countries, stratified cluster sampling design was applied to randomly recruit schools classes. A quota method was applied in the other countries to randomly recruit participants. Details on the intake of all fluid types were obtained with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
85
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 94 publications
(104 citation statements)
references
References 26 publications
8
85
3
Order By: Relevance
“…When accomplished, this method will reduce measurement error, facilitate interpretation of data and allow valid comparisons between population groups and countries. The Liq.In 7 surveys aimed to address these limitations by consistently using a harmonized survey protocol and a 7-day fluid-specific record, in comparisons of TFI and types of beverages consumed by children, adolescents and adults across 13 countries [26][27][28][29] .…”
Section: Current Methodologies For Assessing Tfimentioning
confidence: 99%
“…When accomplished, this method will reduce measurement error, facilitate interpretation of data and allow valid comparisons between population groups and countries. The Liq.In 7 surveys aimed to address these limitations by consistently using a harmonized survey protocol and a 7-day fluid-specific record, in comparisons of TFI and types of beverages consumed by children, adolescents and adults across 13 countries [26][27][28][29] .…”
Section: Current Methodologies For Assessing Tfimentioning
confidence: 99%
“…In 7 surveys did not meet the adequate intake for water from fluids derived from EFSA [24]. Focusing on the quality of fluid intake, these surveys demonstrated that the contribution of SSB and fruit juices to TFI in children exceeded that of water in 6 out of 13 countries [25]. Moreover, 55% of children and adolescents in the sample consumed more than 1 serving of SSB daily, while up to 21% did not drink water on a daily basis in some countries (unpublished data).…”
Section: Water and Fluid Intake Habits Of Childrenmentioning
confidence: 99%
“…In 12 out of 13 datasets analyzed by Iglesia et al [4], estimated water intakes are below the EFSA standards for over 20 % of children and adolescents. In many countries, drinking water accounts for less than half of reported fluid intake for children [5]. Overall, only 40 % of men and 60 % of women surveyed appear to meet the acceptable intakes for water intake from fluids as set by EFSA [6].…”
mentioning
confidence: 98%
“…Iglesia et al [4], Guelinckx et al [5], and Ferreira-Pêgo et al [6] describe absolute and relative water intake in children, adolescents, and adults from surveys with similar 7-day water intake assessment methodologies in 13 countries.…”
mentioning
confidence: 99%